2005
DOI: 10.1111/j.1365-2966.2004.08592.x
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of pulsar winds with interstellar medium: numerical simulation

Abstract: A time‐dependent numerical simulation of relativistic wind interaction with interstellar medium was performed. The winds are ejected from the magnetosphere of rotation‐powered pulsars. The particle flux in the winds is isotropic while the energy flux is strongly anisotropic. Pure hydrodynamical winds and magnetized winds with magnetization in the range 3 × 10−3–10−1 were modelled. The numerical solutions reproduce the most spectacular features observed in the central part of the plerions: toroidal structure an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
77
1

Year Published

2005
2005
2017
2017

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(85 citation statements)
references
References 54 publications
7
77
1
Order By: Relevance
“…As its free-flowing equatorial wind encounters the more slowly-expanding nebula, a termination shock is formed. Particles accelerated at the shock form a toroidal structure, while some of the flow is collimated along the rotation axis, possibly contributing to the formation of jet-like structures (Bogovalov et al 2005). These structures generate synchrotron radiation that is observed most readily in the X-ray band ( Fig.…”
Section: Observed Properties Of Young Pwnementioning
confidence: 99%
“…As its free-flowing equatorial wind encounters the more slowly-expanding nebula, a termination shock is formed. Particles accelerated at the shock form a toroidal structure, while some of the flow is collimated along the rotation axis, possibly contributing to the formation of jet-like structures (Bogovalov et al 2005). These structures generate synchrotron radiation that is observed most readily in the X-ray band ( Fig.…”
Section: Observed Properties Of Young Pwnementioning
confidence: 99%
“…Although electrons and positrons from magnetospheric electromagnetic cascades escape with relatively low energy from the pulsar light cylinder, where the ratio σ L of electromagnetic energy density to particle energy density must be much larger than unity (σ L ∼ 10 4 for the Crab pulsar [22] this σ parameter must reduce drastically beyond the light cylinder for two reasons: (i) [65] have shown that the Crab pulsar's radio pulses would have been smeared unless the Lorentz factor of the e ± wind exceeds 10 4 ; (ii) Observations at the pulsar wind shock indicate that this ratio must have reduced to σ ∼ 3 × 10 −3 for the Crab [44,17], but in the range 0.01 to 0.1 for the Vela PWN shock [59,17]. The reader is referred to [11] for a review of this particle energization process.…”
Section: Particle Acceleration At Pwn Shocksmentioning
confidence: 99%
“…The magnetic compression ratio 1 < κ < 3 [44] depends on the strength of this relativistic shock (and hence σ). For strong shocks (σ ≪ 1) we have κ ∼ 3, whereas κ ∼ 1 for weaker Vela-like shocks [44], where σ ∼ 0.01 to 0.1 [59,17]. The expression for the maximum particle energy for remnants with field strengths weaker than the Crab (i.e.…”
Section: The Gyroradius Limitmentioning
confidence: 99%
See 1 more Smart Citation
“…Detailed morphological studies with Chandra revealed a complex structure of PWNe, such as, e.g., the torus-plus-jet structure in the Crab Nebula [7]. In general, young pulsars show an axial symmetry around what is believed to be the pulsar rotation axis [8,9,10,11]. Spatially-resolved measurements by XIPE will determine the magnetic field orientation and the level of turbulence in the torus, the jet, and at various distances from the pulsar.…”
Section: Acceleration Process In Pwne and Snrs Observed By Xipe Xipe mentioning
confidence: 99%